1984
DOI: 10.1258/002367784780864866
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus pneumonia in guineapigs: an experimental reproduction of the disease

Abstract: The recently described virus-induced pneumonia in guineapigs (Naumann et al., 1981) was experimentally reproducible in newborn animals, though not in preadult animals. Baby hamsters and newborn rats were also not susceptible to infection. 10 of 11 infected newborn guineapigs developed pathological changes identical with those found in spontaneous cases. The incubation period was from 5 to 10 days. The agent could not be cultivated in vitro, and therefore no applicable serological tests could be established. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Adenoviridae: guinea pig adenovirus (GPAdV) BACKGROUND Virus-associated necrotizing bronchopneumonia in guinea pigs is a spontaneous multifactorial disease that has low morbidity, high mortality, and a worldwide distribution (Percy and Barthold, 2007). After the first description in Germany and experimental reproduction of the disease (Kunstyr et al, 1984;Naumann et al, 1981), sporadic spontaneous cases were reported from the United States, Australia, and Switzerland (Brennecke et al, 1983). A 10-year endemic "in-house" occurrence of adenovirus-associated disease was reported in a British pharmaceutical research facility.…”
Section: Dna Virusesmentioning
confidence: 99%
“…Adenoviridae: guinea pig adenovirus (GPAdV) BACKGROUND Virus-associated necrotizing bronchopneumonia in guinea pigs is a spontaneous multifactorial disease that has low morbidity, high mortality, and a worldwide distribution (Percy and Barthold, 2007). After the first description in Germany and experimental reproduction of the disease (Kunstyr et al, 1984;Naumann et al, 1981), sporadic spontaneous cases were reported from the United States, Australia, and Switzerland (Brennecke et al, 1983). A 10-year endemic "in-house" occurrence of adenovirus-associated disease was reported in a British pharmaceutical research facility.…”
Section: Dna Virusesmentioning
confidence: 99%
“…It should be noted that there are reports in the literature describing infection with adenoviruses in guinea pigs without any concurrent clinical signs [25,26]. In addition, in experimental infection of guinea pigs with adenovirus-infected crude suspensions of lung tissue, only newborn guinea pigs (2-3 days old) displayed any clinical signs [27], suggesting other factors such as altered immune status are needed to induce adenoviral respiratory disease.…”
Section: Respiratory Disease In Guinea Pigsmentioning
confidence: 99%